Effect of Clostridium butyricum Supplementation on in vitro Rumen Fermentation and Microbiota With High Grain Substrate Varying With Media pH Levels - Jiao, Peixin; Wang, Ziwei; Wang, Xin; Zuo, Yanan; Yang, Yuqing; Hu, Guanghui; Lu, Changming; Xie, Xiaolai; Wang, Li; Yang, Wenzhu (Frontiers in Microbiology, 2022)
Clostridium butyricum (C. butyricum) can survive at low pH, and it has been widely used as an alternative to antibiotics for the improvement of feed efficiency and animal health in monogastrics. A recent study suggested that the improved ruminal fermentation with supplementing C. butyricum is may be associated with increasing the abundance of rumen microbiota in Holstein heifers, as ruminal pH plays a key role in rumen microbiota and the probiotics are often active in a dose-dependent manner. The objective of this study was to determine the effects of increasing the doses of C. butyricum on gas production (GP) kinetics, dry matter disappearance (DMD), fermentation characteristics, and rumen microbiota using a high grain substrate in batch culture varying with media pH levels. The doses of C. butyricum were supplemented at 0 (control), 0.5 × 106, 1 × 106, and 2 × 106 CFU/bottle, respectively, at either media pH 6.0 or pH 6.6. The fermentation microbiota at 0 and 1 × 106 CFU/bottle were determined using the 16S rRNA high throughput sequencing technology. Overall, the GP, DMD, total volatile fatty acid (VFA) concentration, and the ratio of acetate:propionate were higher (P <0.01) at media pH 6.6 than at pH 6.0. However, there was interaction between pH × dose of C. butyricum for rate constant of GP (P = 0.01), average GP rate (P = 0.07), and volume of GP (P = 0.06); with the increase in C. butyricum supplementation, the GP kinetics were not changed at media pH 6.0, but the volume (P = 0.02), rate of GP (P = 0.01), and average GP rate (P = 0.01) were quadratically changed at media pH 6.6. The DMD was not affected by increasing the supplementation of C. butyricum. The molar proportions of propionate (P <0.09), butyrate (P <0.06), and NH3-N concentration (P = 0.02) were quadratically changed with increasing supplementation of C. butyricum regardless of media pH levels. The interactions between media pH level and dose of C. butyricum supplementation were noticed for alpha diversity indexes of Shannon (P = 0.02) and Evenness (P = 0.04). The alpha diversity indexes increased (P <0.05) except for Chao1 with supplementation of C. butyricum. The unweighted uniFrac analysis showed that the group of control at media pH 6.0 and control at media pH 6.6, and supplementation of C. butyricum and control at media pH 6.0 clustered separately from each other. At the phylum level, relative abundance (RA) of Bacteroidota was lower (P <0.01) and Firmicutes was higher (P <0.01) at media pH 6.6 than pH 6.0. Moreover, RA of Proteobacteria decreased (P <0.05) with supplemented C. butyricum at either media pH 6.6 or pH 6.0. At media pH 6.6, RA of Rikenellaceae_RC9_gut_group and Prevotella were decreased, and CAG-352 was increased (at genus level) compared to pH 6.0. Supplementation of C. butyricum decreased RA of Rikenellaceae_RC9_gut_group and increased CAG-352 at media pH 6.0. It could hence be concluded that manipulating media pH level and supplementation of C. butyricum effectively modulated in vitro rumen fermentation characteristics and microbiota but in a dose depending manner of C. butyricum addition.